2010
DOI: 10.1177/082585971002600404
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of place of Death for recipients of Home-Based Palliative Care

Abstract: Introduction: Health system restructuring combined with the preferences of many terminally ill care recipients and their caregivers has led to an increase in home-based palliative care, yet many care recipients die within institutional settings such as hospitals. This study sought to determine the place of death and its predictors among palliative care patients with cancer. Methods: Study participants were re cruited from the Temmy Latner Centre for Palliative Care, a regional palliative care program based in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
4
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 36 publications
0
52
4
15
Order By: Relevance
“…9,11,22,[27][28][29] The data from our study were in contrast with those of the previous national survey, which showed that half of the patients following the CSMBS died in public hospitals. 16 We found no such association between the types of health-care insurance and home death.…”
Section: Discussioncontrasting
confidence: 81%
“…9,11,22,[27][28][29] The data from our study were in contrast with those of the previous national survey, which showed that half of the patients following the CSMBS died in public hospitals. 16 We found no such association between the types of health-care insurance and home death.…”
Section: Discussioncontrasting
confidence: 81%
“…Assessment of the reliability and validity of the AHCR demonstrated that there was agreement between participants' reports and administrative data (kappa ranging from 0.41 to 1.00). 10 The AHCR has been used in numerous other studies, for a wide range of patient populations and clinical settings 7,[11][12][13][14][15][16][17] The Palliative Performance Scale (PPS) was used to collect data on functional and cognitive status of the patient during each caregiver interview. 18 The PPS assesses the physical functioning in ambulation, activity, and evidence of disease, ability for self-care, intake (i.e., person's eating habits), and level of consciousness.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The paradox is that while there is strong evidence suggesting that the majority of such patients do not want to die either in the ED, ICU or hospital ward, there is very limited information about strategies for out of hospital care in the ED [3, 70, 79, 142, 147, 148]. …”
Section: Resultsmentioning
confidence: 99%